A flatness index for axial-plane morphometric characterization of the zygomatic arch on cone-beam computed tomography - Aslıhan Akbulut; Kaan Orhan; Burak Karip (BMC Oral Health, 2026)
Abstract Objective Quantitative characterization of zygomatic arch geometry remains limited by the lack of a simple dimensionless descriptor applicable to standardized axial imaging. This study aimed to develop and preliminarily evaluate a Flatness Index (FI) to quantify the axial-plane flatness of the zygomatic arch in cone-beam computed tomography (CBCT) images. Methods In this retrospective study, 200 CBCT scans (100 females and 100 males; 18–65 years) were analyzed. The FI was calculated bilaterally on standardized axial CBCT images using the formula FI = 1 − (CD/AB), where AB represents the chord length between the anterior and posterior roots of the zygomatic arch, and CD denotes the maximum perpendicular distance from the arch convexity to the chord. Sex-related differences were assessed using independent-samples t-tests, and right–left differences were evaluated using paired-samples t-tests. A sex-by-side effect was examined by comparing within-subject right-minus-left FI differences between sexes. Age was treated as a continuous variable, and its association with bilateral mean FI was evaluated using Pearson’s correlation and linear regression. Results A statistically significant sex-related difference was observed on the left side ( p < 0.001; Cohen’s d = 0.71), whereas the corresponding difference on the right side did not reach statistical significance ( p = 0.062; Cohen’s d = 0.27). The within-subject right-minus-left FI difference differed significantly between sexes ( p < 0.001; Cohen’s d = 0.62), indicating a significant sex-by-side effect. No significant overall right–left difference was observed ( p = 0.059). Age was not significantly correlated with bilateral mean FI ( r = − 0.094, p = 0.185). Intraobserver reliability was excellent (ICC = 0.94), demonstrating high within-observer repeatability. Conclusion The proposed Flatness Index provides a simple, dimensionless approach for describing axial-plane zygomatic arch flatness and demonstrated excellent intraobserver repeatability in the present dataset. The FI should be interpreted as an axial-plane morphometric descriptor rather than as a measure of true three-dimensional curvature. Interobserver reproducibility and external validity remain to be established.